Carboxymethyl chitosan nanoparticles coupled with CD59-specific ligand peptide for targeted delivery of C-phycocyanin to HeLa cells - Peng Yang; Bing Li; Qi-Feng Yin; Yu-Juan Wang (Tumor Biology)
The combination of nanotechnology and medicine will be the next generation of vehicles for targeted drug delivery. Carboxymethyl chitosan loaded with the anticancer drug C-phycocyanin and the CD59-specific ligand peptide for cancer cell targeting were used to create C-phycocyanin/carboxymethyl chitosan–CD59-specific ligand peptide nanoparticles using the ionic-gelation method. Optimal synthesis conditions, selected by response surface methodology, comprised the ratio carboxymethyl chitosan:C-phycocyanin = 3:1, and carboxymethyl chitosan and CaCl 2 concentrations of 2.0 and 1.0 mg/mL, respectively. The resulting nanoparticles were spherical, with diameters of approximately 200 nm; the entrapment efficient was about 65%; and the drug loading was about 20%. The release of C-phycocyanin from C-phycocyanin/carboxymethyl chitosan nanoparticles was pH sensitive and had a sustainable effect in vitro. Guided by the CD59-specific ligand peptide, the nanoparticles efficiently targeted the surface of HeLa cells and had an obvious inhibitory effect on HeLa cell proliferation as determined by methyl thiazolyl tetrazolium assays. The nanoparticles were hemocompatible and induced apoptosis by upregulation of cleaved caspase-3 and cleaved polyADP-ribose polymerase proteins, and downregulation of Bcl-2 proteins. Our study provides a novel approach to the research and development of marine drugs, and support for targeted therapy using anticancer drugs.